Happiness: Before and after the kids - Mikko Myrskylä; Rachel Margolis (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Understanding how having children influences the parents' subjective well-being (happiness) has great potential to explain fertility behavior. We study parental happiness trajectories before and after the birth of a child using large British and German longitudinal data sets. We account for unobserved parental characteristics using fixed-effects models and study how sociodemographic factors modify the parental happiness trajectories. Consistent with existing work, we find that happiness increases in the years around the birth of the first child, then decreases to before-child levels. Moreover, happiness increases before birth, suggesting that the trajectories may capture not only the effect of the birth but also the broader process of childbearing which may include partnership formation and quality. Sociodemographic factors strongly modify this pattern. Those who have children at older ages or have more education have a particularly positive happiness response to a first birth, and although the first two children increase happiness, the third does not. The results are similar in Britain and Germany and suggest that up to two, children increase happiness, and mostly among those who postpone childbearing. This pattern is consistent with the fertility behavior emerging during the second demographic transition and provides new insights into low and late fertility.
Keywords: 330; fertility; well-being; life course; parenthood